DEVELOPMENT OF WOMEN POSITION IN THE PATRILINEAL INHERITANCE OF INDONESIAN SOCIETY - Elfrida R Gultom (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Patrilineality is a kinship system which is based on paternal line; therefore, the position of men in inheritance law is dominant. Batak, Karo and Bali communities are among those who apply this system. Consequently, this system influences women’s standing in terms of inheritance. This paper discusses women position in inheritance of patrilineal system on those three societies as well as the factors which influence the development of women’s inheritance right. Some principles of this system are maintained while some others change. Several Supreme Court Decisions related to inheritance distribution dispute between men and women have tended to adopt a parental system which gives equality, humanity, justice, and right equality. Supreme Court places women in a neutral position which means that there is modernization which leads to homogeneity, indicating showing equality between men and women as well as providing a significant impact on inheritance law sector in Batak, Karo, and Bali. Keywords: indigenous people, matrilineal, Patrilineal, inheritance, inheritance system